Effect of Ba-substitution on the structure and properties of Pb 0.8Ba0.2[(In1/2Nb1/2) 1-xTix]O3 ceramics - S. Wongsaenmai (2018)
Ferroelectric ceramics with formula Pb0.8Ba 0.2[(In1/2Nb1/2)1-xTi x]O3 (PBINT) (x=0.0,0.1,0.2,0.3,0.4 and 0.5) were prepared via a two-step solid state reaction method. It was found that ceramics with compositions in the range of x=0.0 ∼ 0.3 showed a pseudo-cubic structure, whereas the ceramic with x=0.5 displayed a tetragonal structure. All compositions showed significant frequency dispersion in their dielectric properties. The remanent polarization Pr as well as the coercive field Ec, measured at room temperature, increases with the Ti content. The experimental results obtained in this system are summarized into a phase diagram, with the morphotropic phase boundary (MPB) located at x=0.4. Compared with the Pb[(In1/2Nb1/2)1-xTi x]O3 solid solution system, incorporating Ba in the A-site leads to a significant decrease in the dielectric maximum temperature T max, a suppression of the dielectric relaxation parameter γ, and a shift of the MPB composition to a higher Ti content. © Springer-Verlag 2007.